Generative design in civil construction: a case study in Brazil - Oscar, Luiz Henrique; Cerqueira, Lucas Cecílio; Cunha, Pedro Henrique; Qualharini, Eduardo Linhares (Frontiers in Built Environment, 2023)
The civil construction industry has a significant role in the socioeconomic development of a country and seeks to understand the emerging technologies of computational resources, such as artificial intelligence and that are inserted in design processes, whose stages influence all the constructive quality. This work has to investigate the generative design, in an approach of projects aided by algorithms. Recent new breakthroughs related to Generative Design have the potential to change the way in the construction area drastically. This paper provides a new view of building construction. Thus, through exploratory research based on application examples and a case study, this study presents innovative aspects of Generative Design for construction projects.